Trade and Development Report 2020 - United Nations Conference on Trade; Development (United Nations, 2020)
Drawing on the ideas and proposals presented in previous editions of the Report, this year’s Report analyses the economic impact of the Covid-19 (coronavirus) global pandemic and possible responses that could be both effective and inclusive. It examines different recovery scenarios and, in particular, highlights the danger of a lost decade, addresses immediate difficulties facing developing countries as they well as some of the underlying conditions that, if left unaddressed, will prevent a better recovery. It also discusses some of the institutional changes needed at the international level to bolster recovery and transition to a more socially caring and environmentally sustainable global economy – a transition that the world needed before the pandemic but has become ever more pressing.